Stability in the Xi Era: Trends in Ethnic Policy in Xinjiang and Tibet Since 2012. (June 2019) - Godbole, Avinash
This article looks at major trends in China's minority policy under Xi Jinping. It studies various methods implemented in order to control the unrest including the usage of technology for the purpose of monitoring people's digital and geographic footprints. It studies development versus stability debate and takes a cursory look at how BRI intersects the identity question. It also looks at various debates underway among the Chinese intelligentsia on the proper handling of the minority issue. Trend shows that under Xi, China's ethnicity policy has hardenened is based on ensuring that the ethnic minority groups identify themselves as Chinese first before being Uighurs or Tibetans.